Harnessing endoscopic ultrasound-guided radiofrequency ablation to reshape the pancreatic ductal adenocarcinoma microenvironment and elicit systemic immunomodulation - Vishali Moond; Bhumi Maniyar; Prateek Suresh Harne; Jennifer M. Bailey-Lundberg; Nirav C. Thosani (Open Exploration Publishing Inc., 2024)
Pancreatic ductal adenocarcinoma (PDAC) is characterized by poor prognostics and substantial therapeutic challenges, with dismal survival rates. Tumor resistance in PDAC is primarily attributed to its fibrotic, hypoxic, and immune-suppressive tumor microenvironment (TME). Endoscopic ultrasound-guided radiofrequency ablation (EUS-RFA), an Food and Drug Administration (FDA)-approved minimally invasive technique for treating pancreatic cancer, disrupts tumors with heat and induces coagulative necrosis, releasing tumor antigens that may trigger a systemic immune response-the abscopal effect. We aim to elucidate the roles of EUS-RFA-mediated thermal and mechanical stress in enhancing anti-tumor immunity in PDAC. A comprehensive literature review focused on radiofrequency immunomodulation and immunotherapy in pancreatic tumors to understand the pathophysiological mechanisms of RFA and its effect on the TME, which could prevent recurrence and resistance. We reviewed clinical, preclinical, and in vitro studies on RFA mechanisms in pancreatic adenocarcinoma, discussing the unique immunomodulatory effects of EUS-RFA. Recent findings suggest that combining RFA with immune adjuvants enhances responses in pancreatic adenocarcinoma. EUS-RFA offers a dual benefit against PDAC by directly reducing tumor viability and indirectly enhancing anti-tumor immunity. Observations of neutrophil-mediated immunomodulation and programmed cell death ligand 1 (PD-L1) modulation support integrating EUS-RFA with targeted immunotherapies for managing pancreatic adenocarcinoma. Integrating EUS-RFA in PDAC treatment promises direct cytoreduction and synergistic effects with molecular targeted therapies. Prospective clinical trials are crucial to assess the efficacy of this combined approach in improving outcomes and survival rates in advanced PDAC cases.